2022
DOI: 10.18261/njdl.17.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Technology and knowledge. In what way are knowledge and teachers’ knowledge practices in subject areas crucial for the integration of technology in education?

Abstract: In recent decades, education has undergone a digital transformation. In Norway, the government's digitalization strategy for education includes ambitious goals and plans, with expectations of new forms of teaching and learning, better learning, and improved learning outcomes. Despite the increased availability of technology in Norwegian schools, there is still a significant gap between available technology in the classroom and teachers' use of this technology for educational purposes. This paper is based on Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Lie [14,20] found a lack of time for designing and implementing WebQuest projects in the classroom among preservice science teachers. Some in-service language teachers did not have adequate time to explore digital libraries or use them to enhance their teaching; according to Lie [14] in their study, Bratland [25] reported that some in-service mathematics teachers did not have time to learn and use GeoGebra software.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lie [14,20] found a lack of time for designing and implementing WebQuest projects in the classroom among preservice science teachers. Some in-service language teachers did not have adequate time to explore digital libraries or use them to enhance their teaching; according to Lie [14] in their study, Bratland [25] reported that some in-service mathematics teachers did not have time to learn and use GeoGebra software.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it may be used to visually represent, explore, or prove geometric relationships, properties, and theorems. This approach may teach mathematical subjects [7,25,28]. You can manage and deliver online courses with multiple modules and activities with the Moodle Learning Management System.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes technology a basic need for everyone so that it can be said that between educational innovation and educational technology is a unity that cannot be separated (Salsabila & Agustian, 2021). As in the 21st century, when information and technology have dominated all aspects of life including affecting education, therefore every element in the scope of education must be responsive in adapting to this rapid development (Bratland et al, 2022;Elmira et al, 2022). Being responsive to changing times also means having to understand what the dynamics of education are demanding that will continue to develop (Galvis & Carvajal, 2022).…”
Section: Introductionmentioning
confidence: 99%